2012
DOI: 10.4148/2378-5977.7089
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Xylanase in high-co-product diets on nutrient digestibility in finishing pigs (2012)

Abstract: A total of 36 pigs (PIC 337 Ã-1050; initially 185 lb BW) were used in a 14-d study to evaluate the effects of xylanase (Porzyme 9302; Danisco Animal Nutrition, St. Louis, MO) in growing-finishing diets varying in dietary fiber on nutrient digestibility. Pigs were randomly allotted to 1 of 6 dietary treatments in a 2 Ã-3 factorial. Main effects were increasing dried distillers grains with solubles (DDGS; 35, 42.5, and 50%) with or without xylanase (0 or 4,000 units xylanase per kilogram of diet. The 6 treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…However, the effects of adding NSP-degrading enzymes to corn DDGS-based diets for pigs have been inconsistent; most studies did not report increased energy and nutrient digestibilities in pigs fed corn DDGSbased diets due to supplemental NSP-degrading enzymes. For instance, addition of xylanase (Asmus et al, 2012;Ndou et al, 2015;Jang et al, 2016;Moran et al, 2016) or a product that contained xylanase, β-glucanase, and cellulase activities (Rho et al, 2017(Rho et al, , 2018 to corn-soybean meal (SBM)corn DDGS-based diets for pigs did not affect apparent total tract digestibility (ATTD) of GE.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effects of adding NSP-degrading enzymes to corn DDGS-based diets for pigs have been inconsistent; most studies did not report increased energy and nutrient digestibilities in pigs fed corn DDGSbased diets due to supplemental NSP-degrading enzymes. For instance, addition of xylanase (Asmus et al, 2012;Ndou et al, 2015;Jang et al, 2016;Moran et al, 2016) or a product that contained xylanase, β-glucanase, and cellulase activities (Rho et al, 2017(Rho et al, , 2018 to corn-soybean meal (SBM)corn DDGS-based diets for pigs did not affect apparent total tract digestibility (ATTD) of GE.…”
Section: Introductionmentioning
confidence: 99%
“…DDGS-based diets supplemented with fiber-degrading enzymes (Widyaratne et al, 2009;Asmus et al, 2012;Kerr and Shurson, 2013). Moreover, we recently reported that feeding growing pigs corn DDGS steeped with a combination of commercial fiber degrading enzymes for 24 h did not improve ileal or total digestibility of nutrients, fiber and energy relative to control corn DDGS steeped with no enzymes (Rho et al, 2018).…”
mentioning
confidence: 99%
“…() found a positive effect of xylanase addition on apparent faecal ADF digestibility in growing–finishing pigs fed a diet containing 15% or 30% cDDGS; however, the enzyme did not improve body weight gain (BWG), FI, feed conversion ratio (FCR), carcass quality or the digestibility of other nutrients. Results of a study with finishing pigs indicated that increasing levels of DDGS in the diet (35–50%) reduced the apparent faecal digestibility of DM, fat, GE, ADF, NDF, Zn, Ca and P (Asmus et al., ). Xylanase addition did not, however, increase the availability of nutrients (Asmus et al., ).…”
Section: The Effects Of Nsp‐hydrolysing Enzymes (Carbohydrases)mentioning
confidence: 99%
“…Results of a study with finishing pigs indicated that increasing levels of DDGS in the diet (35–50%) reduced the apparent faecal digestibility of DM, fat, GE, ADF, NDF, Zn, Ca and P (Asmus et al., ). Xylanase addition did not, however, increase the availability of nutrients (Asmus et al., ). An experiment by Yoon et al.…”
Section: The Effects Of Nsp‐hydrolysing Enzymes (Carbohydrases)mentioning
confidence: 99%